Growth hormone and the risk of atherosclerosis in growth hormone-deficient children. Issue 6 (December 2015) - Binay, Cigdem; Simsek, Enver; Yıldırım, Ali; Kosger, Pelin; Demiral, Meliha; Kılıç, Zubeyir
Abstract: Objective: Growth hormone-deficient (GHD) children have been found to have higher cardiovascular mortality rates and an increased carotid intima-media thickness (CIMT). This study investigated the risk of atherosclerosis and the effect of recombinant growth hormone (rhGH) replacement therapy on the lipid profile and CIMT in GHD children. Design: A total of 40 GHD children (mean age: 12.3 ± 2.04 years) were investigated before and after 1 year of rhGH therapy at a dosage of 0.03 mg/kg/day and 40 age- and sex-matched healthy children (mean age: 12.1 ± 2.23 years) were enrolled as a control group, in the same pubertal stage. Fasting blood samples were obtained for lipid profile, IGF-1, and IGFBP-3 analyses. The patients and controls underwent CIMT measurements before and after 1 year of rhGH treatment. Results: The growth velocity and height standard deviation scores increased significantly over 1 year of treatment in all patients. The total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, and atherogenic index (Ai) values were increased while the high-density lipoprotein (HDL) cholesterol value was decreased in the GHD children, as compared to the controls; however, the triglyceride (TG) level was comparable. After 1 year of treatment, a significant decrease in the TC, LDL cholesterol, and Ai values as well as a significant increase in the HDL value were observed in the GHD patients, with the values becoming similar to those in the control group. The mean CIMT was significantly greater in the GHD subjects than in the controls. After 1 year of therapy, the CIMT in the GHD subjects had decreased significantly; however, it was still greater than that in the control group. IGF-1 was negatively correlated with TC, LDL cholesterol, Ai, right CIMT, and left CIMT. Conclusions: GHD is associated with increased atherosclerotic risk in children. An improved lipid profile and CIMT were detected after 1 year of hormone replacement therapy. Highlights: This study investigated the risk of atherosclerosis and the effect of rhGH administration on the lipid profile and CIMT in GHD children.